Genome sequence of the acid-tolerant strain Rhizobium sp. LPU83 - Wibberg, Daniel (2014)
Rhizobia are important members of the soil microbiome since they enter into nitrogen-fixing symbiosis with different legume host plants. Rhizobium sp. LPU83 is an acid-tolerant Rhizobium strain featuring a broad-host-range. However, it is ineffective in nitrogen fixation. Here, the improved draft genome sequence of this strain is reported. Genome sequence information provides the basis for analysis of its acid tolerance, symbiotic properties and taxonomic classification.